From Global Archives to Grassroots Mobilization: The Evolution of Feminist Movements in International and Nepali Contexts - Sapkota, Yamuna (NPRC Journal of Multidisciplinary Research, 2025)
This study investigates how international women’s movements have shaped women’s political participation in Nepal, analyzing the complex interplay of gender, caste, ethnicity, and class. Spanning from the 1940s democratic movements to the post-2006 constitutional reforms, the research traces the development of feminist consciousness, legal frameworks, and grassroots activism in Nepal. While international instruments like CEDAW (1992) and domestic gender quotas (e.g., 33% representation in the Constituent Assembly) have formalized women’s political inclusion, substantive equality remains elusive due to entrenched patriarchal norms, caste-based discrimination, and linguistic barriers. Employing qualitative methods—including archival research and policy analysis—the study demonstrates that despite increased institutional representation, Dalit, Janajati, and Madhesi women continue to face systemic marginalization. The findings highlight a critical disconnect between global feminist paradigms and Nepal’s intersectional realities, calling for context-sensitive strategies that address overlapping oppressions. The paper concludes with policy recommendations to strengthen legal enforcement, amplify marginalized voices, and transform symbolic representation into meaningful political empowerment.